Perceptual attunement in vowels: A meta‐analysis. (23rd November 2013) - Tsuji, Sho; Cristia, Alejandrina
ABSTRACT: Although the majority of evidence on perceptual narrowing in speech sounds is based on consonants, most models of infant speech perception generalize these findings to vowels, assuming that vowel perception improves for vowel sounds that are present in the infant's native language within the first year of life, and deteriorates for non‐native vowel sounds over the same period of time. The present meta‐analysis contributes to assessing to what extent these descriptions are accurate in the first comprehensive quantitative meta‐analysis of perceptual narrowing in infant vowel discrimination, including results from behavioral, electrophysiological, and neuroimaging methods applied to infants 0–14 months of age. An analysis of effect sizes for native and non‐native vowel discrimination over the first year of life revealed that they changed with age in opposite directions, being significant by about 6 months of age. © 2013 Wiley Periodicals, Inc . Dev Psychobiol 56: 179–191, 2014.